Sustained censorship in AZ (2026-02) (Azerbaijan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Azerbaijan. Data sourced from OONI.
Censorship Incident ID: AZ-2026-0329. Severity: critical. Confidence: 85%